Bifurcation of Function in Four Dimensions With Eight Parameters Based on Lyapunov-Schmidt Reduction - Madhi, Zainab S.; Hussain, Mudhir A. Abdul (Communications in Mathematics and Applications, 2021)
In this paper, we investigate the bifurcation-spreading of critical points for a certain smooth function with eight parameters which have codimension 80. In addition, we found five plots of caustic (bifurcation set) corresponding different cases of parameters. Finally, using the method of alternative problems (Lyapunov-Schmidt method) we obtained the bifurcation solution for the equation of sixth order with boundary conditions as applicable.